Assessment of renal function in living kidney donors before and after nephrectomy: A Japanese prospective, observational cohort study. (28th February 2019) - Kakuta, Yoichi; Imamura, Ryoichi; Okumi, Masayoshi; Horio, Masaru; Isaka, Yoshitaka; Ichimaru, Naotsugu; Takahara, Shiro; Nonomura, Norio; Tanabe, Kazunari
Abstract : Objective: To investigate the utility of estimated glomerular filtration rate for assessing kidney function in living kidney donors before and after nephrectomy. Methods: A total of 101 donors underwent inulin clearance measurements before and 1 year after nephrectomy. The mean of three inulin clearance values was used as the measured glomerular filtration rate. Estimated glomerular filtration rate based on serum creatinine and cystatin C levels was calculated using the Japanese estimated glomerular filtration rate equation, Chronic Kidney Disease Epidemiology Collaboration formula and new full age spectrum equation. Age‐adjusted chronic kidney disease was defined as glomerular filtration rate <75 mL/min/1.73m 2 for donors aged <40 years, <60 mL/min/1.73m 2 for donors aged 40–65 years and <45 mL/min/1.73m 2 for donors aged >65 years. Results: The postoperative measured glomerular filtration rate <60 mL/min/1.73m 2 and age‐adjusted chronic kidney disease rate were 36.0% and 27.0%, respectively. In younger donors (aged <50 years), postoperative measured glomerular filtration rate <60 mL/min/1.73m 2 and age‐adjusted chronic kidney disease rates were 5.3% and 26.3%, respectively. In older donors (aged >70 years), postoperative measured glomerular filtration rate <60 mL/min/1.73m 2 and age‐adjusted chronic kidney disease rates were 75.0% and 33.3%, respectively. Donor age and measured glomerular filtration rate were significant predictors of postoperative measured glomerular filtration rate. The Japanese estimated glomerular filtration rate equation based on creatinine and cystatin C showed the strongest correlation with measured glomerular filtration rate. However, the Japanese estimated glomerular filtration rate equation based on creatinine overestimated the prevalence of measured glomerular filtration rate <60 mL/min/1.73m 2, whereas the Japanese estimated glomerular filtration rate based on cystatin C underestimated it. Conclusions: Aged donors might have an increased risk of lower glomerular filtration rate after donor nephrectomy; post‐surgery, long‐term monitoring of renal function is recommended. Measurement of glomerular filtration rate should be carried out for donors, especially pre‐surgery. A more precise glomerular filtration rate equation is required in the future.